2012
DOI: 10.1105/tpc.112.103374
|View full text |Cite
|
Sign up to set email alerts
|

Verticillium Infection Triggers VASCULAR-RELATED NAC DOMAIN7–Dependent de Novo Xylem Formation and Enhances Drought Tolerance in Arabidopsis  

Abstract: The soilborne fungal plant pathogen Verticillium longisporum invades the roots of its Brassicaceae hosts and proliferates in the plant vascular system. Typical aboveground symptoms of Verticillium infection on Brassica napus and Arabidopsis thaliana are stunted growth, vein clearing, and leaf chloroses. Here, we provide evidence that vein clearing is caused by pathogen-induced transdifferentiation of chloroplast-containing bundle sheath cells to functional xylem elements. In addition, our findings suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 52 publications
1
106
0
Order By: Relevance
“…The different ways by which drought modulates plant's interactions with these pathogens are discussed. Apart from the above-mentioned two scenarios, pathogens can enhance the resistance of plants to drought (Reusche et al 2012;Xu et al 2008). However, this aspect is not discussed in this chapter.…”
Section: Drought Modulates Plant-pathogen Interactionmentioning
confidence: 98%
“…The different ways by which drought modulates plant's interactions with these pathogens are discussed. Apart from the above-mentioned two scenarios, pathogens can enhance the resistance of plants to drought (Reusche et al 2012;Xu et al 2008). However, this aspect is not discussed in this chapter.…”
Section: Drought Modulates Plant-pathogen Interactionmentioning
confidence: 98%
“…Recent work on infection with the vascular pathogen Verticillium longisporum has shown modification of tissue architecture, probably as a compensatory measure to counteract these negative effects. Bundle sheath cells of infected Arabidopsis thaliana and Brassica napus plants undergo transdifferentiation into functional xylem elements (Figure 1m), which increases drought tolerance (Reusche et al 2012). Interestingly, V. longisporum does not colonize plant parts above the hypocotyl.…”
Section: Tissue Transdifferentiationmentioning
confidence: 98%
“…Seven putative NAC (for NAM, ATAF1/2, and CUC2) transcription factors have been identified in Arabidopsis thaliana, which are involved in transdifferentiation and fall into the VND subfamily (Vascular related NAC Domain) (Demura et al 2002;Kubo et al 2005;Yamaguchi et al 2010). Within this subfamily, VND6 and VND7 seem to have specific roles on Verticillium-triggered transdifferentiation of bundle sheath cells, with VND6 regulating metaxylem (xylem tissue that consists of rigid thick-walled cells and occurs in parts of the plant that have finished growing) formation, and VND7 inducing protoxylem (the firstformed xylem tissue, consisting of extensible thin-walled cells thickened with rings or spirals of lignin) development (Kubo et al 2005;Reusche et al 2012). Interestingly, homologs of NAC domain protein genes (PtVNS/ PtrWND) have been identified in poplar (Populus trichocarpa) and their role in differentiation of the xylem vessel element has been demonstrated (Hu et al 2010;Ohtani et al 2011).…”
Section: Reactions Of Infected Trees and Recoverymentioning
confidence: 99%
“…In vascular diseases of annual plants, it has been observed that infection may induce transdifferentiation of bundle sheath cells to novel, functional xylem vessels, or may increase xylem cells within the vascular bundle as a result of prolonged or renewed activity of the vascular cambium (Reusche et al 2012). This phenomenon allows novel vegetative growth of affected stems and branches and enhances recovery (Tjamos et al 1991;López-Escudero and Blanco-López 2001).…”
Section: Reactions Of Infected Trees and Recoverymentioning
confidence: 99%